La violación al principio de igualdad en la suspensión de la sustanciación del proceso en los delitos de violencia intrafamiliar. - Macías Hinojoza, Omar Stalin (2024)
Through the study on the principle of equality in the suspension of the conduct of the procedure, in crimes of intrafamily violence, which is established in Art.- 651.3 of the Comprehensive Organic Criminal Code, it was established that there is a violation of the principles of equality, due process and legal certainty by denying authorization for the defendant to agree to the suspension of the conduct of the procedure. Through the investigative design, through interviews with legal professionals such as: Judges, Prosecutors and Public Defenders, of the Guaranda canton, allowed us to determine exactly that the crimes of intrafamily violence must be understood as a subject that involves the human species, since the damage and consequences caused by violence in general, go far beyond physical damage, and involve a spiral of violence, in which it increases until it even causes death, violence that not only affects women, but men, when they respond to certain stereotypes called social convention, they make, like the law, behaviors based on gender stereotypes sanctioned, leaving the detriment of allowing only the victim to have the application of the institution from the suspension to the conduct of the procedure. Keywords: Violence, principle of equality, gender, due process.